The relation of biomedicine to beauty clinics - Srisawat, Thanavot (Journal of Multidisciplinary Academic Research and Development (JMARD), 2023)
The objectives of this study were (1) to study the status of biomedicine underlying beauty clinics, and (2) to study the dynamic associations between science and technology studies (STS) with qualitative research and linked actor-network theory (ANT) to analyze and explain relevant phenomena. Results were that biomedical social relations were not merely about treating or nurturing patients, but also pertained to beauty, relationships based on beauty conditions, and a series of interactions with animate and inanimate entities essential for constructing an esthetic beauty, including doctors, patients, salespeople, and medical technology. These findings suggest that inanimate participants were key factors in biomedical science as indispensable for constructing biomedical reality and relationships.